An appraisal of interrogational torture in liberal democracy - Ezeogu, Uchenna Azubuike (International Journal of Humanities and Social Science Research, 2016)
The idea of torture has long been prohibited by; the Geneva Conventions, The U N convention Against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment, and The European Convention for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment. So many other international treaties have placed absolute prohibition on torture and it has been championed by countries that claim to be liberal democracies, yet we still see and notice traces of torture in almost all the liberal democratic countries. Could it be that torture is a necessary evil that cannot be avoided? Why the ban on torture? Can torture ever be justified; why and why not? Are liberal democratic principles compatible with the idea of torture? Is there any contradiction in punishing those who choose to break the law in order to protect the state? The question of torture has posed serious challenge to liberal democracies. We shall in this research consider why in spite of various bans on torture by most liberal democracies, it’s still very much prevalent. The paper suggests that given to extenuating circumstances, interrogational torture maybe permissible.
Keywords: terrorism; Torture; Liberal Democracy; Interrogational torture